Pengaruh Model Pembelajaran Berbasis Masalah (PBL) dengan Media Animasi Terhadap Hasil Belajar Siswa Kelas V SD pada Materi Sistem Tata Surya - Maheswari, Alesia Nala; Oktavia, Rani; Setiyawan, Hery (Indo-MathEdu Intellectuals Journal, 2025)
The material of the solar system tends to be abstract so that it is difficult for students to understand, especially if it is delivered using conventional methods. The PBL model emphasizes the active involvement of students in solving real problems, while animation media helps visualize abstract concepts. This study aims to determine the effect of the Problem-Based Learning (PBL) model assisted by animation media on the learning outcomes of fifth grade elementary school students on the material of the solar system. This study used a quasi-experimental method with a Nonequivalent Control Group design. The subjects of the study consisted of two classes, namely Class V A with 25 students as an experimental class using the PBL model with animation media and Class V B with 25 students as a control class using conventional methods. Data collection was carried out through pre-test and post-test tests, observation, and documentation. The results of the t-test showed a significant difference between the learning outcomes of the two groups after treatment, with a significance value of 0.001 (p <0.05). These results indicate that the application of the PBL model assisted by animation media has a positive effect on improving student learning outcomes. This study recommends the application of innovative learning models to improve the effectiveness of science learning in elementary schools